Indonesia dan Persaingan di Era Asean Economic Community - Hendra Maujana Saragih (Universitas Muhammadiyah Surabaya, 2017)
Abstract This paper focusing on looking at Indonesia's readiness to deal with the Era of the Economic Community in ASEAN with the urgency that Indonesia's preparations should have a systemic impact on Indonesia's economic growth. The socialization that has been carried out continues and continues to be inflated by every child of the nation so as not to lose compete and be swallowed by the existence of regional countries that really use ASEAN Economic Community as a positive and constructive economic opportunity for each ASEAN member country officially. ASEAN Economic Community is one form of Free Trade Area (FTA) and located in Southeast Asia .ASEAN Economic Community which is formed with a mission to make the economy in ASEAN to be better and able to compete with countries whose economy is more advanced than the condition of ASEAN countries currently. The realization of ASEAN Economic Community, can make ASEAN a more strategic position in the international arena. Researchers expect that with the realization of the ASEAN economic community can open the eyes of all parties, resulting in an inter-sectoral dialogue that will also complement each other among the stakeholders of the economic sector in ASEAN countries and this is very inherent formally. Keywords: Competition, Free Trade Area, Opportunity, Challenge